Avaliação da atividade antioxidante, citotóxica e antimicrobiana da espécie amazônica licaria puchury-major (mart.) kosterm - Graça, Rosilane Ramos (2010)
Antioxidants are substances that at low concentrations can inhibit or retard the oxidation of an oxidizable substrate. The cytotoxic activity detects bioactive compounds and aims to assess or predict the toxic effects on biological systems. The antimicrobial activity open perspectives in the development of effective antimicrobial for the treatment of infectious diseases caused by them. In this context the research was conducted botanical species Amazon shares Licaria puchury-major, endemic Borba-AM., Aiming to determine the activities: antioxidant, cytotoxic and antimicrobial activities. The quantification of total phenolics was made by Folin Ciocateau for antioxidant activity methods were DPPH., ABTS+, ß-carotene/linoleic acid system (LPO). The cytotoxicity assays were: lethality with A. saline and the test on the erythrocyte hemolytic camungongos (Mus musculus Swiss). For antimicrobial activity, we used the micro-organism: S. aureus, M. Smegimates, B. cereus, E. coli and C. albicans. The samples tested were: essential oils of flowers and leaves with their respective hydrolates, the DCM and MeOH extracts of leaves, the aqueous extracts of leaves, seeds, stems and branches thin and thick, teas, seeds, leaves, branches thick, thin and crushed leaves. In results of antioxidant evaluation, the sample with the highest total phenolic content was the essential oil of leaves (17.63±0.51mg/GAE). In the DPPH. sample that showed the best activity was the kidnapping of radical leaf essential oil (IC50=6.81mg/mL), and the ABTS method: the aqueous extracts of the stem (IC50=2.66mg/mL) and oil leaf essential (IC50=4.63mg/mL). In the method OLP samples with greater ability to inhibit oxidation were: DCM extract of leaves (61.05±2.54mg/mL), aqueous extracts of the stem (60.82±5.53mg/mL) MeOH extract of leaves (54.55±2.36mg/mL) and essential oil of leaves (53.88±1.93mg/mL). Showed no cytotoxicity in A. saline: all samples of aqueous extracts and hydrolates (> 2000μg/mL). And against the hemolytic test: The best result was the aqueous extract of the stem showing no hemolysis at any concentration. Followed by essential oils from flowers and leaves that showed hemolysis on concentration (1μg/mL) is considered low cytotoxicity. On antimicrobial activity against bacteria B. cereus and S. aureus better than the sample inhibited the halo were essential oils from flowers and leaves, extracts of leaves in DCM and aqueous seed. And against C. albicans yeast extracts in DCM and the aqueous stem and seed. It is concluded that L. puchury-major has antimicrobial and antioxidant potential and may open perspectives for the applicability biotechnology making it necessary to continue the research. Keywords: Antioxidants, cytotoxicity, antimicrobial, Licaria puchury-major